Race and policing in the 2016 presidential election: Black lives matter, the police, and dog whistle politics - Drakulich, Kevin M. (Criminology, 2020)
A series of deaths of Black Americans at the hands of the police sparked mass protests, received extensive media coverage, and fueled a new civil rights movement in the years leading up to the 2016 presidential election. Both major party nominees campaigned on issues of race and policing in different ways. Drawing on colorblind racism theories and the history of law-and-order politics, we explore how views of race relations and the police were associated with voting behavior. We ask, on the one hand, whether people were engaged with the civil rights issues raised by Black Lives Matter and, on the other hand, whether Trump's expressions of support for the police functioned as a racial “dog whistle” to mobilize a particular set of voters. Using the 2016 American National Election Studies (ANES) Time Series Study, we find that concern about biased policing and support for the civil rights movement seeking to address it were associated with increased turnout among Democrats and more votes for Clinton. In addition, consistent with a dog whistle effect, claims of supporting the police were connected to votes for Trump mainly among those with high levels of racial resentment. We conclude by discussing the symbolic role of police in American society and politics.